2013
DOI: 10.1074/jbc.a112.397752
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-mediated allosteric inhibition of caspase-6.

Abstract: PAGE 36002:Equation 2 was printed with mistakes. The correct equation is as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Thus, ZIP10 is a novel survival factor for B-cell progenitors and has a suppressive effect on caspase activity through Zn uptake. Although in vitro studies have previously demonstrated that physiological concentrations of Zn modulate caspase activity (31)(32)(33) cysteine residues in the catalytic domain of caspases inhibits their enzymatic activity (34), it was still elusive how Zn homeostasis modulates caspase-mediated apoptotic signaling in the physiological situation. It is well recognized that rigorous selection processes occur during B-cell maturation, in which down-regulation of the antiapoptotic factor B-cell lymphoma 2 (BCL2) induces apoptosis to prevent the generation and expansion of nonor self-reactive B-cell clones (19,35).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ZIP10 is a novel survival factor for B-cell progenitors and has a suppressive effect on caspase activity through Zn uptake. Although in vitro studies have previously demonstrated that physiological concentrations of Zn modulate caspase activity (31)(32)(33) cysteine residues in the catalytic domain of caspases inhibits their enzymatic activity (34), it was still elusive how Zn homeostasis modulates caspase-mediated apoptotic signaling in the physiological situation. It is well recognized that rigorous selection processes occur during B-cell maturation, in which down-regulation of the antiapoptotic factor B-cell lymphoma 2 (BCL2) induces apoptosis to prevent the generation and expansion of nonor self-reactive B-cell clones (19,35).…”
Section: Discussionmentioning
confidence: 99%
“…This term describes downstream effects mediated through changes in gene expression, not signaling events. Importantly, intracellular zinc signaling targets a number of enzymes involved in cellular signaling, including protein tyrosine phosphatases (PTPs) (41, 448), phosphodiesterases (PDEs) (161, 427), calcineurin (14), caspases (285,423), and various kinases such as mitogen-activated protein kinase (MAPK) and protein kinase C (PKC) (72, 149). Physiological levels of intracellular free Zn 2ϩ concentrations regulate these enzymes, e.g., inhibition of caspase-3, T-cell PTP, and PTP-1B is achieved with IC 50 values below 10, 200, and 17 nM, respectively (140, 266).…”
Section: Zinc Signalingmentioning
confidence: 99%
“…Sulfenation could transiently or locally regulate caspase activity, since all caspases are cysteinyl proteases. While cellular Casp3 is under strong regulation by the inhibitor of apoptosis proteins 41 , Casp1 and Casp6 do not have known cellular protein inhibitors, although Casp6 can be inhibited in an allosteric fashion by phosphorylation and zinc 42,43 . The inhibition of Casp1, Casp3, and Casp6 could have a major influence on inflammation, apoptosis and neurodegeneration, respectively.…”
Section: Discussionmentioning
confidence: 99%